UMP volunteers handle Campus Pantry for students benefit - UMP, PNC (2020)
A total of 200 volunteers consisting of 110 volunteers from UMP Gambang and 90 from UMP Pekan involved in the establishing UMP Campus Pantry at both campuses on 13 March 2020.